AGAMA, SEKOLAH DAN PEMENUHAN HAK: (Telaah Ketersediaan Guru Agama Berbasis Agama Siswa di SD Kabupaten Bangka) - Luna Febriani; Dini Wulansari; Putra Pratama Saputra; Syawaludin (Prodi Sosiologi Agama, 2020)
Indonesia is a country whose population has a variety of religious beliefs, including Islam, Christianity, Catholicism, Buddhism, Hinduism, Confucianism, and others beliefs. The majority of Indonesia's population adheres to Islam. This then makes religious subjects a basic compulsory subject given in schools at every level of elementary, middle school even university. Bangka Regency has 6 religions in accordance with the religions recognized by Indonesia, namely Islam, Buddhism, Hinduism, Catholicism, Protestantism, and Khong Hu Cu. Bangka is one of the districts known for the diversity of trust and upholds the right to respect differences. This research was designed to identify the phenomena occurring which was related to the availability of religious teachers based on the context of fulfilling students' rights to proper religious education for them and to identify the factors influencing the conditions of the application of religious education in elementary schools (SD), both in private schools and state schools, related to the availability of religious teachers who were of the same religion as students. The method used in this research was descriptive qualitative using the perspective of Educational Sociology as the blade of analysis. The results showed that the problems faced in relation to religious subjects faced at primary schools in Bangka were often the subjects taught by teachers who were not competing with them. This then made students with minority religions in the school follow the majority ones' religions or they got the subject from teachers with incapability in religious basis.